2001
DOI: 10.1002/ajh.1176
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of high titer inhibitors in mild hemophilia A with avoidance of factor VIII and immunosuppressive therapy

Abstract: We describe two patients with mild hemophilia A (MHA) who developed high titer inhibitor (HTI) following intensive recombinant factor VIII (rFVIII) concentrate replacement for surgery and trauma. Intranasal desmopressin was instituted shortly following immunosuppressive therapy (IST) and activated prothrombin complex concentrate (APCC) in one case, and following APCC alone in the second case. Avoidance of factor VIII (FVIII) coupled with intranasal desmopressin prophylaxis three times a week resulted in undete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
(31 reference statements)
1
25
0
Order By: Relevance
“…In mild haemophilia complicated by an inhibitor, desmopressin may be effective, as released endogenous FVIII may be less reactive with the inhibitor, when compared with replacement FVIII. A tolerizing effect of treatment with desmopressin has also been reported in this specific patient group [14,15].…”
Section: Desmopressinsupporting
confidence: 64%
“…In mild haemophilia complicated by an inhibitor, desmopressin may be effective, as released endogenous FVIII may be less reactive with the inhibitor, when compared with replacement FVIII. A tolerizing effect of treatment with desmopressin has also been reported in this specific patient group [14,15].…”
Section: Desmopressinsupporting
confidence: 64%
“…Our extended search for inhibitors in relation to continuous infusion of VIII in studies published between 2000 and 2006 revealed six additional case reports [18,[41][42][43][44][45] and three case series [19,20,21 ], comprising a total of 31 patients, aged 0.5-75 years (25 mild/six severe), who developed an inhibitor. All patients received intensive factor replacement for surgery or major bleeds; seven of nine authors reported use of rFVIII; most of the 25 patients with mild hemophilia received less than 30 exposure doses of FVIII before continuous infusion and four were previously untreated patients (PUPs).Table 3shows details of inhibitor development in patients with mild hemophilia in four well documented studies[16 ,18,20,45].…”
mentioning
confidence: 99%
“…The poor response rate to combination treatment most likely represents confounding by indication, i.e., patients with worse disease or a more persistent inhibitor, were more likely to have received several treatments either simultaneously or sequentially. Other single case reports or small case series have reported a positive experience with combination treatments that have included immune suppressive agents such as corticosteroids and/or cyclophosphamide, however, case reports are prone to reporting bias [57]. …”
mentioning
confidence: 99%